Sophisticated educational software for dentistry students using dental measurement system (DEMS) - Noraziah, Ahmad; Siang, Lim Cheh; Abdalla, Ahmed N.; Herawan, Tutut; Tze, Wong Ying; Mohd Helmy, Abd Wahab (Elsevier Ltd., 2011)
Nowadays, the dental society is very successful since the technology they using are very modern and it bring many advantages to the dentist and patient such. Dental Measurement System (DEMS) has been developed as an educational software and technology to be used by the dentist or lecturer, in order to teach the dentistry student about the treatment of tooth decay in International Islamic University Malaysia (IIUM) dental clinic. Through DEMS dentist can obtain accurate tooth decay data analysis compared to the traditional method. DEMS is the supporting system for IIUM dental clinic to computerize the traditional method to ensure the process of tooth decay image clearer. In addition, it provides the calibration and measurement to allow the staff and students IIUM to measure the tooth decay based on image. This system is developed by using the Visual C++ that integrated with OpenCV, which is the library that enable image processing techniques enhance the image.